FETAL CONGENITAL GOITER IN GOAT: A CASE REPORT - KUJUR, ANJU; SRIVASTAVA, N; KUMAR, BRIJESH; JASROTIA, NANCY; ARUNPANDIAN, J; GANESHAN, M (The Indian Journal of Animal Reproduction, 2021)
A Case report of a pregnant doe aged 14 months old enabled to deliver fetus was presented in the Referral Veterinary Polyclinic, ICAR-Indian Veterinary Research Institute, Bareilly. Doe fails to deliver the foetus due to a large increment in the size of the foetus, resulting in dystocia. The doe was treated with PGF2 alpha, estrodiol and velathamate which lead to the opening of the cervix. The presentation of foetus was brought in to normal in the uterus and a dead fetus was successfully removed. The dead fetus had a large swelling in the cranio-ventral neck region with the skin devoid of hair, pale-white and thickened with myxedema indicating congenital goitre. The most prevalent cause of congenital goitre in kids is low iodine intake or dietary iodine deficiency during the third trimester of pregnancy, which results in the birth of a dead or stillborn foetus. Iodine deficient diets, goitrogenic substances that interfere with thyroxinogenesis and excess dietary iodine are the main pathogenic pathways responsible for thyroid hyperplasia. This communication reports a case of dystocia due to congenital goiter in a goat. The defective fetus was delivered successfully by changing its presentation inside the uterus.